2021
DOI: 10.1155/2021/6658321
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Improves Pregnancy Outcomes in Rats with Thin Endometrium by Promoting the Expression of Pinopode‐Related Molecules

Abstract: A thin endometrium affects the success of assisted reproduction due to low endometrial receptivity. Acupuncture improves endometrial receptivity and promotes the formation of pinopodes, the ultrastructure marker implantation window. However, the specific underlying mechanisms remain unclear. In this study, the efficacy of acupuncture treatment and its underlying mechanism were investigated by analyzing pregnancy rate, pinopode formation, and related molecular markers in thin endometrium model rats. Absolute et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…Acupuncture, moxibustion, cupping, acupoint sticking, meridian acupoint massage, and other methods commonly used in traditional Chinese medicine have gradually achieved good auxiliary effects in the treatment of different diseases. In recent years, it has been reported that acupuncture can improve the receptivity of endometrium and promote the formation of pinopodes, leading to increased levels of integrin αvβ3, homeobox A10 (HOXA10), heparin-binding EGF-like growth factor (HBEGF), estrogen receptor alpha (ERα), and progesterone receptor (PR) [ 173 ]. Moreover, the effectiveness of electroacupuncture (EA) in assisted reproduction has also been confirmed [ [174] , [175] , [176] ].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture, moxibustion, cupping, acupoint sticking, meridian acupoint massage, and other methods commonly used in traditional Chinese medicine have gradually achieved good auxiliary effects in the treatment of different diseases. In recent years, it has been reported that acupuncture can improve the receptivity of endometrium and promote the formation of pinopodes, leading to increased levels of integrin αvβ3, homeobox A10 (HOXA10), heparin-binding EGF-like growth factor (HBEGF), estrogen receptor alpha (ERα), and progesterone receptor (PR) [ 173 ]. Moreover, the effectiveness of electroacupuncture (EA) in assisted reproduction has also been confirmed [ [174] , [175] , [176] ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, higher pinopode expression was found in subjects with higher serum P. Compared with P, E did not seem to play a significant role in mediating the therapeutic effects of TEAS. Some animal experiments proved that acupuncture promotes the expression of endometrial LIF during the implantation period [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frequency is one of the key parameters of electroacupuncture stimulation. It has been reported that low frequency electroacupuncture improves endometrial receptivity in hyperovulation cycle [ 34 ], further, Wei Chen et al reported that low-frequency electroacupuncture facilitates implantation by activating the VEGFR2/PI3K/AKT and VEGFR2/ERK signaling pathways to enhance endometrial angiogenesis in a rat model of ovarian hyperstimulation [ 35 ], but that of high-frequency electroacupuncture to endometrial receptivity in hyperovulation cycle remains unknown.…”
Section: Discussionmentioning
confidence: 99%